A simple low-temperature adiabatic calorimeter for small samples - Bagatskii, M.I.; Sumarokov, V.V.; Dolbin, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
A simple adiabatic calorimeter has been made to investigate the heat capacity of small samples (≤ 1 cm3) of carbon nanomaterials in the temperature range from 1 to 300 K. It makes possible: i) short-time mounting of a sample; ii) doping of samples with gases directly in the calorimeter; iii) short-time cooling of a sample down to helium temperatures.The adiabatic calorimeter is suitable to place into a helium vessel of a portable Dewar or a helium cryostat. The heat capacity of the fullerit sample has been measured in the temperature range from 1 to 30 K.